APPLICATION OF FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDES TO FINANCIAL BEHAVIOR WITH FINANCIAL LITERACY AS AN INTERVENING VARIABLE: CASE STUDY ON STUDENTS OF STIE SAKTI ALAM KERINCI - Elvia Desi, Dona; Ali, Hapzi (Qawwam : The Leader's Writing, 2025)
This study discusses the application of financial knowledge, financial attitudes towards financial behavior with financial literacy as an intervening variable (Case Study on STIE Sakti Alam Kerinci Students). The purpose of this study is to determine the application of financial knowledge, financial attitudes towards financial behavior with financial literacy as an intervening variable. The research method used is quantitative. The sample in this study was 103 people. The sampling technique used accidental sampling. The data used in this study is primary data, which was obtained from a questionnaire submitted to STIE Sakti Alam Kerinci students. The results of this study include: 1) Financial Knowledge has a significant effect on Financial Literacy, 2) Financial Attitude does not have a significant effect on Financial Literacy, 3) Financial Knowledge has a significant effect on Financial Behavior, 4) Financial Attitude has a significant effect on Financial Behavior, 5) Financial Literacy has a significant effect on Financial Behavior, 6) Financial literacy does not have a significant direct effect on the influence of Financial Knowledge on financial behavior and 7) Financial literacy does not have a significant direct effect on the influence of Financial Attitude on financial behavior